Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1091/mbc.e16-09-0672
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of contractile forces: the missing piece in cell mechanics

Abstract: Mechanical forces are key regulators of cell and tissue physiology. The basic molecular mechanism of fiber contraction by the sliding of actin filament upon myosin leading to conformational change has been known for decades. The regulation of force generation at the level of the cell, however, is still far from elucidated. Indeed, the magnitude of cell traction forces on the underlying extracellular matrix in culture is almost impossible to predict or experimentally control. The considerable variability in mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 120 publications
1
24
0
Order By: Relevance
“…The tension in SFs tends to reflect the mechanics of the environment in which cells are embedded. Cells growing in rigid matrices or within tissues that are being stretched build F-actin networks under increased tension 20,43,44 . Recent work has shown that matrix mechanics controls the nuclear localization of the LIM protein FHL2 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The tension in SFs tends to reflect the mechanics of the environment in which cells are embedded. Cells growing in rigid matrices or within tissues that are being stretched build F-actin networks under increased tension 20,43,44 . Recent work has shown that matrix mechanics controls the nuclear localization of the LIM protein FHL2 45 .…”
Section: Discussionmentioning
confidence: 99%
“…where G * represents actin with no bound nucleotide. Following [39], this reaction is approximated as a one-step irreversible reaction with ATP and ADP included explicitly, Equation 33. We can write the rate k nex of this approximate reaction as:…”
Section: • Nucleotide Exchangementioning
confidence: 99%
“…To produce effective morphological changes, the magnitude and spatial distribution of contractile forces must be regulated and integrated over distances that are much longer than individual filaments (Agarwal and Zaidel-Bar, 2019;Murrell et al, 2015). However, the mechanism regulating the production and transmission of local forces throughout the cell is still poorly understood (Burridge and Guilluy, 2016;Kurzawa et al, 2017;Livne and Geiger, 2016). The progress in understanding this integration process has notably been limited by the technical challenges to manipulate the network locally while simultaneously measuring the impact on force production at the level of the entire cell.…”
Section: Introductionmentioning
confidence: 99%